POLA PENYEBARAN SERANGAN RINTISAN KUMBANG AMBROSIA PLATYPUS TREPANATUS PADA DOLOK KAYU RAMIN - Paimin Sukartana; A Martawijaya (Jurnal Penelitian Hasil Hutan, 1987)
The distribution  pattern  of  the initial attack  of  ambrosia  beetles Platypus trepanatus   Chap. (Coleoptera:  Platypodidae) on  ramin  logs (Gonystylus  bancanus  Kurz.s ) was studied.  Six fresh  cut  test  logs,  each of  about  25 cm  in diameter  and 50 cm  in  length,  were barked  and horizontally  kept in a row of 20 cm apart at about 75 cm above the ground on a pair of sleepers. The surface of each log was longitudinally  divided into eight equal parts,  i.e. two single ones of the top and bottom face and three paired others situated of the upper sides, sides, and lower sides.The result showed that the attacks were not equally scattered over the whole face  of the logs. The most violent attack  was found  on both the upper side parts.  The number of  tunnels  on these parts  were significantly  different   than  those  on the others.  The lighter infested parts  were respectively recorded on the side, top, lower sides, and  bottom face of the logs. More than 90%  of the initial infestations  were concentrated on the upper side and side parts,  covering 50%   of the surface area of a log.